2011
DOI: 10.1186/1687-9856-2011-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Vitamin D deficiency in infancy: daily 400 IU vitamin D is sufficient

Abstract: SummaryAim-objectiveVitamin D deficiency and rickets in developing countries continues to be a major health problem. Additionally, the increase of cases of rickets in children of some ethnic groups in the United States and European countries has provided this issue to be updated. Obviously, powerful strategies are necessary to prevent vitamin D deficiency nation-wide. In 2005, a nationwide prevention program for vitamin D deficiency was initiated, recommending 400 IU vitamin D per a day.This study was designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 20 publications
3
38
0
5
Order By: Relevance
“…But the reasons proposed by other studies, that boys tended to spend longer periods of time outdoors with less frequent use of sunscreen23-26), were not appropriate for our results. Our subjects were 1 to 6 months aged infants, who live indoors all day long, regardless of sex27). In this situation, this difference between two sex was so notable that it needs to recognize other influencing factor in the following study.…”
Section: Discussionmentioning
confidence: 98%
“…But the reasons proposed by other studies, that boys tended to spend longer periods of time outdoors with less frequent use of sunscreen23-26), were not appropriate for our results. Our subjects were 1 to 6 months aged infants, who live indoors all day long, regardless of sex27). In this situation, this difference between two sex was so notable that it needs to recognize other influencing factor in the following study.…”
Section: Discussionmentioning
confidence: 98%
“…In this program, the recommended daily vitamin D dose is 400 IU, which is compatible with the “Institute of Medicine (IOM) Committee’s http://www.nationalacademies.org/hmd/ 2011 Report on Dietary Reference Intakes for Calcium and Vitamin D”. This dose was chosen also because a daily 400 U supplementation of vitamin D was shown to be adequate to provide a serum 25(OH)D level >15 ng/mL in >90% of all infants (7,8). In a large scaled survey study by the Ministry of Health to evaluate the success of the nationwide program, it was shown that of 2504 infants aged between 6 and 17 months, serum 25(OH)D level was >15 ng/mL in 73.6% (9).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, similar to our results, it was found that the frequencies of vitamin D deficiency and insufficiency in infants aged 3-18 months were 4.7 % and 7.1 %, respectively. 16 However, in a study conducted in our region in healthy children 400 IU/day vitamin D supplementation dose in the first year was insufficient; 25(OH)D levels in 30 % of the children aged 12-24 months were reported to be below 15 ng/mL. 17 The results of that study were quite different from our results, possibly due to the fact that the children included in that study were only fed with breast milk and did not receive formula.…”
Section: Discussionmentioning
confidence: 99%